Proses Adaptasi Mahasiswa Perantauan di UIN Ar-Raniry - Fathurrahman Helmi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This study aims to describe the causes behind the process of culture shock among overseas students in Banda Aceh to describe the process of cultural adaptation and its impact on overseas students at UIN Ar-Raniry. This research uses a qualitative approach with a phenomenological study. Data collection techniques used in this study were interviews and documentation. The results of the study explained that there were 5 stages experienced by overseas students in cultural adaptation. The two key informants had expectations when they were going abroad and had motives to study in college and achieve their goals, this was also included in the honeymoon stage. The process of interaction and lectures abroad results in a phase of frustration where there are many differences between hometowns and overseas cities so that there is a need for adjustments to new things overseas until there are exchanges in terms of culture, ethics and meaning, these things include in the readjustment stage. At the resolution stage, the two key informants decided to stay overseas to complete their studies